ChemInform Abstract: Reinvestigation of Np2Se5: A Clear Divergence from Th2S5 and Th2Se5 in Chalcogen—Chalcogen and Metal—Chalcogen Interactions. Issue 39 (5th September 2013) - Jin, Geng Bang; Hu, Yung‐Jin; Bellott, Brian; Skanthakumar, S.; Haire, Richard G.; Soderholm, L.; Ibers, James A.
Abstract Single crystals of Np2Se5 are prepared from the elements in Sb2Se3 flux (sealed silica tube, 1223 K, 48 h).